Treatment and prognosis of mature T-cell and NK-cell lymphoma: an analysis of patients with T-cell lymphoma treated in studies of the German High-Grade Non-Hodgkin Lymphoma Study Group - Schmitz, Norbert; Trümper, Lorenz; Ziepert, Marita; Nickelsen, Maike; Ho, Anthony Dick; Metzner, Bernd; Peter, Norma; Loeffler, Markus; Rosenwald, Andreas; Pfreundschuh, Michael (Blood, 2010)
Mature T-cell and natural killer (NK)–cell lymphomas are rare and heterogeneous diseases following an aggressive clinical course which necessitates immediate therapy. Outcome is generally believed poor although only 1 recent study1 comprises all major T-cell lymphoma subtypes according to the World Health Organization classification2,3 with spin-off studies reporting on clinical outcome and prognostic factors of various subtypes. In contrast to the progress made in the treatment of aggressive B-cell lymphoma, evidence for similar therapeutic improvements in T- and NK-cell lymphoma is largely absent. Therefore, we analyzed a large cohort of patients with T-cell lymphoma who have been treated on protocols of the German High-Grade Non-Hodgkin Lymphoma Study Group (Deutsche Studiengruppe Hochmaligne Non-Hodgkin Lymphome [DSHNHL]). We were particularly interested in the long-term results achieved with “standard” CHOP (cyclophosphamide, hydroxydaunorubicin (doxorubicin), Oncovin (vincristine), and prednisone/prednisolone) and CHOP-like therapy and wanted to define prognostic factors which should influence the decision which patients should be treated on standard or experimental protocols in the future.
Gesehen am 20.06.2023